Inactivation of Pseudomonas aeruginosa biofilms by thymoquinone in combination with nisin - Chen, Hong; Ji, Peng-Cheng; Qi, Yue-Heng; Chen, Shi-Jin; Wang, Chang-Yao; Yang, Yu-Jie; Zhao, Xin-Yu; Zhou, Jin-Wei (Frontiers in Microbiology, 2023)
Pseudomonas aeruginosa is one of the most important foodborne pathogens that can persist in leafy green vegetables and subsequently produce biofilms. In this study, the synergistic effect of thymoquinone and nisin in reducing biofilm formation of P. aeruginosa on lettuce was evaluated, and their anti-virulence and anti-biofilm mechanisms were also investigated. At concentrations ranging from 0.5 to 2 mg/mL, thymoquinone inhibited the production of autoinducers and virulence factors and enhanced the susceptibility of P. aeruginosa biofilms to nisin as evidenced by the scanning electron microscopy and confocal laser scanning microscopy. Integrated transcriptomics, metabolomics, and docking analyses indicated that thymoquinone treatment disrupted the quorum sensing (QS) system, altered cell membrane component, and down-regulated the expressions of genes related to virulence, efflux pump, and antioxidation. The changed membrane component and repressed efflux pump system enhanced membrane permeability and facilitated the entrance of nisin into cells, thus improving the susceptibility of biofilms to nisin. The dysfunctional QS and repressed antioxidant enzymes lead to the enhancement of oxidative stress. The enhanced oxidative stress disrupted energy metabolism and protein metabolism, ultimately attenuated the virulence and pathogenicity of P. aeruginosa PAO1. Our study indicated that thymoquinone has the potential to function as a QS-based agent to defend against foodborne pathogens.